De toren als theoretisch probleem in de classicistische bouwkunst. Een verkenning in de hoogte (Bulletin KNOB, 1996)
The architecture of ancient Hellas and Rome had a strongly horizontal character. The most monumental type of building from this cultural sphere - the classical temple - bears witness to this. From the Renaissance, when throughout Europe this classical architecture was the source of inspiration for contemporary building, the temple was the pre-eminent aesthetic ideal. Consequently, its proportions, which were considered harmonious, were in principle also normative for completely different types of building created later and indispensable ever since.One of these types of building which had become enormously popular after Antiquity was the tower - a major heritage from the Middle Ages which people were reluctant to part with when building churches and town halls even after 1500, particularly north of the Alps. The tower was pre-eminently a vertical building, so that it could only with great difficulty fit in with the architecture of the Renaissance, Baroque and Classicism, inspired as it was by the classical heritage.The theme of this essay is the question how this contradiction between a tradition, necessary for a tower, and a theory which could not quite cope with it, was reconciled in The Netherlands in the sixteenth, seventeenth and eighteenth centuries. The fact is that even leading treatise writers in Italy, France and Germany were not able to come up with a satisfactory answer to this question, while others for the same reason conveniently ignored the whole problem and make no mention at all of the phenomenon tower. In Dutch practice too, it was only rarely that a solution was found resulting in a 'classical' tower that was more or less satisfactory both from an aesthetic and a theoretical point of view.Nevertheless, on the basis of the international 'Vitruvian' theory of architecture, as it gradually developed after 1500, a number of rules were formulated which a 'classical' tower - just as any other 'classical' building - had to comply with. However, some of these rules proved to be conflicting, when superposition of columns or pilasters was applied in order to subdivide a tower into various floors. Exact measures were laid down for each of the five types of columns, which left little space when various types were superpositioned, and in combination with other rules, such as a gradually decreasing height of the floors, resulted in a knot that could hardly be disentangled.When testing Dutch towers from the period of the Dutch Republic for compatibility with these rules, even the work of renowned architects, such as Hendrick de Keyser or Arent van 's-Gravensande fails as not much better than unskilled labour. In the early eighteenth century some Gerrnan authors, such as Sturm and Decker, were to find ingenious solutions, but these were too complicated and costly to apply in The Netherlands. At the end of the century their compatriot Samuel Locke went farthest in his search for a both beautiful and classically sound tower. He devoted an entire folio volume with numerous tables to it, in vain, for his own final project makes it clear that a really 'classical' tower can actually not exist.